Clinical Study on the Prevention of Oxaliplatin-Induced Neurotoxicity with Guilongtongluofang: Results of a Randomized, Double-Blind, Placebo-Controlled Trial. (13th November 2013) - Liu, Yunfang; Zhu, Guangying; Han, Li; Liu, Jie; Ma, Ting; Yu, Huiming
Abstract : Objective . Oxaliplatin-induced peripheral neurotoxicity continues to be a kind of frequent dose-limiting toxicity for many cancer patients. This study evaluated the preventive effects of Guilongtongluofang on peripheral neurotoxicity induced by oxaliplatin in patients with colorectal tumor. Patients and Methods . From May 2007 to May 2011, we conducted a randomized, double-blind, placebo-controlled trial. 120 patients of colorectal cancer treated with adjuvant oxaliplatin-based chemotherapy were randomly enrolled into the trial group and the control group. The trial group received Guilongtongluofang (at a dose of 200 mL once a day) from 3 days prior to chemotherapy. The control group received a placebo from 3 days prior to chemotherapy. Every 2-week cycle, neurotoxicity was evaluated using numeric rating scale for pain intensity and experienced relief. The primary endpoint was efficacy measurement which included oxaliplatin-induced neurotoxicity and tumor response. The differences of side effects between the two groups were also analyzed. Results . The percentage of grades 1-2 neurotoxicity was significantly lower in the trial group than that in the control group (13.3% versus 20.0%; P < 0.05 ) after two cycles of treatment. The difference of the percentage of neurotoxicity between the two groups was significant after six cycles (51.7% versus 70.0%; P < 0.05 ). Significant difference for the mean time to the development of grade 1+ neurotoxicity was found between the two groups (9.4 w in the trial group versus 6.5 w in the control group, P < 0.05 ). The cumulative incidence of grade 1 or more sensory neurotoxicity was significantly lower in the trial group than that in the control group (P < 0.05 ). No significant differences of tumor response rate were found between the two groups the trial group and the control group. No significant difference was found between the trial group and the control group (all P > 0.05 ). Conclusion . This study provides evidence that Guilongtongluofang is a promising drug for the prevention of oxaliplatin-induced neurotoxicity in patients with colorectal cancer, and it does not reduce the efficacy of oxaliplatin.